Energy planning of sustainable districts: Towards the exploitation of small size intermittent renewables in urban areas. (15th October 2018) - Bracco, Stefano; Delfino, Federico; Ferro, Giulio; Pagnini, Luisa; Robba, Michela; Rossi, Mansueto
Highlights: Optimization model to design a sustainable energy district. Sizing of distributed resources on multiple sites. Use of photovoltaic, wind and cogeneration power plants. Intermittent nature and uncertainties in renewable sources. Application to three urban test-bed sites. Abstract: An optimization model is formalized for the energy planning of urban districts equipped with renewable energy power plants (photovoltaic fields and wind micro-turbines), combined heat and power units, and traditional boilers; districts are connected to the public distribution grid. The main decision variables of the model are the number and typology of wind turbines and cogeneration plants, the size of photovoltaic fields and the power exchange with the public grid. The optimal values of the variables come from the minimization of installation, maintenance and operational costs, and satisfy load and technical constraints. The model is applied to three districts in the Savona Municipality that represent pilot sites of an extended project concerning the planning and management of smart urban areas. The analysis of different scenarios allows evaluating the role of uncertainties of renewable sources over the optimal solution of the planning problem.